2019
DOI: 10.1155/2019/9497861
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Dietary Factor Assessment Tool for Evaluating Associations between Visceral Fat Accumulation and Major Nutrients in Japanese Adults

Abstract: Background and Objectives. The increased prevalence of metabolic syndrome necessitates the establishment of tools for evaluating dietary factors associated with visceral fat accumulation and preventing visceral fat obesity. Here, we aimed to develop a dietary factor assessment tool for evaluating visceral fat accumulation. Methods. We conducted a dietary habit questionnaire survey and visceral fat measurement by bioelectrical impedance analysis in 11,438 adults (Survey 1) and a dietary habit questionnaire surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 15 publications
3
12
0
Order By: Relevance
“…On the other hand, for senior females, the effect of dietary PFC composition on VFA levels is not clear. The relationship between a higher ratio of %P to %F and lower VFA observed in young and middle-aged males is consistent with another study of the Japanese population (21). Moreover, studies indicating that Canadian subjects with a high protein diet have less body fat (24) and that European and Brazilian subjects in six studies with a high-protein diet have higher energy expenditure (25) are also consistent with our results.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…On the other hand, for senior females, the effect of dietary PFC composition on VFA levels is not clear. The relationship between a higher ratio of %P to %F and lower VFA observed in young and middle-aged males is consistent with another study of the Japanese population (21). Moreover, studies indicating that Canadian subjects with a high protein diet have less body fat (24) and that European and Brazilian subjects in six studies with a high-protein diet have higher energy expenditure (25) are also consistent with our results.…”
Section: Discussionsupporting
confidence: 93%
“…Respondents aged 20 to 34 were defined as "young, " those 35 to 59 as "middle-aged, " and those 60 or older as "senior." Age 35 was set as a boundary because visceral fat begins to accumulate at approximately this age in the general Japanese population (21). Age 60 was set as a boundary for seniors because people typically begin to retire from full-time work at this age, and most women have reached menopause.…”
Section: Discussionmentioning
confidence: 99%
“…Eating speed was associated with carbohydrate/fiber intake in men. Previous studies revealed that carbohydrate/fiber intake is associated with metabolic syndrome [27] and visceral fat accumulation [42]. Thus, there is a possibility that poor diet quality in men with the habit of fast eating is the cause of the presence of NAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…Some epidemiologic studies, including cross-sectional studies [10,11,12,13,14,15,16,17,18,19] and longitudinal studies [20,21,22,23,24], have investigated the association between nutritional components or foodstuff and VFA. These analyses indicated that only dietary fiber [17,21,23], carotenoid [15] and calcium [16,22] were negatively associated with VFA in terms of nutritional components.…”
Section: Introductionmentioning
confidence: 99%